A Model of Goal Directed Vegetable Parenting Practices - Hingle, Melanie (2011)
The aim of this study was to explore factors underlying parents’ motivations to use vegetable parenting practices (VPP) using the Model of Goal Directed Vegetable Parenting Practices (MGDVPP) (an adaptation of the Model of Goal Directed Behavior) as the theoretical basis for qualitative interviews. In-depth interviews with parents of 3–5-year-old children were conducted over the telephone by trained interviewers following a script. MGDVPP constructs provided the theoretical framework guiding script development. Audio-recordings were transcribed and analyzed, with themes coded independently by two interviewers. Fifteen participants completed the study. Interviews elicited information about possible predictors of motivations as they related to VPP, and themes emerged related to each of the MGDVPP constructs (attitudes, positive anticipated emotions, negative anticipated emotions, subjective norms, and perceived behavioral control). Parents believed child vegetable consumption was important and associated with child health and vitality. Parents described motivations to engage in specific VPP in terms of emotional responses, influential relationships, food preferences, resources, and food preparation skills. Parents discussed specific strategies to encourage child vegetable intake. Interview data suggested parents used diverse VPP to encourage child intake and that varied factors predicted their use. Understanding these factors could inform the design of interventions to increase parents’ use of parenting practices that promote long-term child consumption of vegetables.